2018
DOI: 10.22631/rr.2018.69997.1050
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A gene polymorphism at position G197A and systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a multi-systemic disorder with various clinical manifestations. Lupus is a multifactorial autoimmune disease resulting from complex gene-environment interactions. IL-17 is a pro-inflammatory cytokine secreted by Th-17 cells, and IL-17A and IL-17F are two predominant members of this family. The present study assessed the association of IL-17F (rs763780) gene polymorphism with SLE. A total of 102 SLE patients and 141 healthy subjects were enrolled in this case-control study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Our findings were in agreement with Sharifzadeh et al, (2018). His case-control study involved 102 SLE patients and 141 healthy control subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were in agreement with Sharifzadeh et al, (2018). His case-control study involved 102 SLE patients and 141 healthy control subjects.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, Sharifzade et al. 27 reported that the IL-17 rs2275913 A allele may be protective against SLE in an adult Iranian population. Ethnic background or gene–environmental interplay as well as variations in studied age group and cohort size may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, the IL-17A polymorphisms have been linked with human autoimmune disorders such as rheumatoid arthritis, autoimmune thyroid disease, ulcerative colitis and adult-onset SLE. 2326 Only a few studies have examined the association between the IL-17 SNPs and susceptibility to adult-onset SLE and LN, 26 , 27 with conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…27 In contrast, it offered marginal protection against SLE development in an Iranian cohort. 28 Furthermore, there was no significant association between IL-17A rs2275913 polymorphism and SLE in two independent studies from Mexico 29 and the Bulgarian population. 30 One of the key reasons for these inconsistencies is the use of smaller sample sizes, which results in a decreased power of the study to detect any possible genetic link.…”
Section: Introductionmentioning
confidence: 95%